Pengaruh Pengeluaran Pemerintah Dan Investasi Swasta Terhadap Pertumbuhan Ekonomi Dan Kesempatan Kerja Di Kabupaten Malinau (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
This study aims to determine the effect of government spending and private investment to economic growth and employment opportunities in Malinau. Collected at the Central Statistics Agency (BPS).Analysis of data using path analysis (path analysis). The results showed that government spending and private investment directly not significant effect on economic growth. Government spending and growth is directly aekonomi not significant effect on employment, while private investments have a significant effect on employment in Malinau .